Anti-static crystal diamond coating and preparation method thereof

By using inorganic emulsions and acrylic emulsions as substrates in inorganic imitation stone coatings, and adding tin oxide as antistatic agents, combined with other fillers and additives, the problems of coatings in terms of electrostatic, flexibility and weather resistance are solved, and efficient antistatic effects and safety are achieved.

CN119912830APending Publication Date: 2025-05-02TIANJIN DEPUWEI COATINGS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510248588.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Existing inorganic imitation stone coatings have problems in storage, flexibility, weather resistance and static electricity, especially in winter, where static electricity problems are more prominent.

Method used

Inorganic emulsions and acrylic emulsions are used as substrates, and tin oxide is added to the coating as an antistatic agent. Combined with bentonite, filler and modifier, a coating with high conductivity and density is formed.

Benefits of technology

It improves the anti-static effect of the paint, reduces the generation of electrostatic sparks, enhances the safety and fire resistance of the paint, and improves the flexibility and weather resistance of the paint.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of interior wall stone-like coatings, and particularly discloses an anti-static crystal diamond coating and a preparation method thereof. The anti-static crystal diamond coating comprises the following raw materials in parts by weight: 40-50 parts of acrylic emulsion; 115 to 125 parts of an inorganic emulsion; 0.8 to 1.0 part of bentonite; 2-3 parts of a thickening agent; 2-4 parts of a suspending agent; 1.5 to 2.5 parts of a bactericide; 0.1 to 0.5 part of a multifunctional auxiliary agent; 0.8 to 1.0 part of a coalescing agent; 0.8 to 1.0 part of a defoaming agent; 2-5 parts of an antistatic agent; 200 to 210 parts of a filling material; 122 to 123 parts of water; the antistatic agent comprises tin oxide. The anti-static crystal diamond coating can be used in an interior wall stone-like coating, and has the advantages of being anti-static, durable, pollution-resistant, scratch-resistant, water-resistant, color-retaining and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of interior wall imitation stone coatings, and more specifically, to an antistatic crystal diamond coating and a preparation method thereof. Background Art

[0002] Limited by factors such as materials, technology, and cost, there are not many inorganic imitation stone coatings on the market, and there are even fewer products that can meet the indicators of safety, environmental protection, and fire prevention. Most inorganic imitation stone coatings are realized by directly using inorganic emulsions, but the direct use of inorganic emulsions will bring problems such as storage, flexibility, weather resistance, long film formation time, and low early strength. In addition, considering the static electricity problem caused by seasonal changes, especially in winter, the static electricity problem is even more difficult to guard against and very annoying. Therefore, there is an urgent need for an inorganic imitation stone coating with an antistatic effect. Summary of the invention

[0003] In order to improve the static electricity problem of coatings, the present application provides an anti-static crystal diamond coating and a preparation method thereof.

[0004] The present application provides an anti-static crystal diamond coating, which adopts the following technical solution: In a first aspect, the present application provides an antistatic crystal diamond coating, comprising the following raw materials in parts by weight: 40-50 parts of acrylic emulsion; 115-125 parts of inorganic emulsion; 0.8-1.0 part of bentonite; 2-3 parts of thickener; 2-4 parts of suspending agent; 1.5-2.5 parts of fungicide; Multifunctional additive 0.1-0.5 parts; Film-forming aid 0.8-1.0 part; Defoaming agent 0.8-1.0 part; 2-5 parts of antistatic agent; 200-210 parts of filler; 122-123 parts of water; The antistatic agent includes tin oxide.

[0005] By adopting the above technical scheme, the technical scheme of the present application preferably adopts inorganic emulsion and acrylic emulsion as the base material of the coating, which can make the coating obtain excellent characteristics such as better flexibility, weather resistance and high strength. At the same time, the present application preferably adopts tin oxide added to the coating as an antistatic agent. Tin oxide has the advantages of excellent conductivity, high specific surface area, etc., which can improve the conductivity of the coating, thereby improving the antistatic effect of the coating, so that when the coating is applied to interior wall coating, the generation of static sparks is reduced, that is, the safety and fireproof effect of the coating are better. At the same time, with the cooperation of bentonite, filler and antistatic agent, a gradation effect can be formed in the coating, and the compactness of the coating formed by the coating is improved.

[0006] Optionally, the filler includes crystal diamond and sintered sand.

[0007] By adopting the above technical scheme, crystal diamond has a shiny appearance and excellent thermal conductivity, while sintered sand has good fire resistance, wear resistance and other effects. It is preferred to use crystal diamond and sintered sand as fillers, which can give the coating excellent wear resistance, fire resistance and shiny effects, greatly improving the decorativeness and color diversity of the coating.

[0008] Optionally, the filler is a modified filler modified by a modifier, and the modifier is a tin-containing modifier.

[0009] By adopting the above technical scheme, it is preferred to modify the filler with a tin-containing modifier. The tin-containing modifier can introduce tin atoms into the filler. Due to the excellent conductive effect of the tin atoms themselves, the filler obtains a conductive effect, and the filler network in the coating is transformed into a filler-conductive network, further improving the antistatic effect of the coating.

[0010] Optionally, the modification treatment steps are as follows: mixing the filler with water to obtain a mixture, adding a tin-containing modifier and ammonia water to the mixture, adjusting the pH, putting it into a reactor for reaction, drying, washing, filtering, and drying to obtain a modified filler.

[0011] By adopting the above technical solution, under alkaline conditions and a suitable pH environment, the tin-containing modifier can evenly form a coating layer on the surface of the filler, so that the filler obtains a conductive effect and constructs a conductive network, effectively improving the antistatic effect of the coating.

[0012] Optionally, the coverage rate of the modified filler is 26-30%.

[0013] By adopting the above technical scheme, the coverage rate of the modified filler is optimized. At an appropriate coverage rate, the migration of free electrons between particles is not restricted, and a uniform electron migration channel is formed between the particles. In addition, the resistivity of the filler at this coverage rate is relatively low, and it is not easy to agglomerate, so that the filler can be evenly dispersed in the coating and build a stable conductive network, so that the coating has an excellent antistatic effect.

[0014] Optionally, the modifier further includes any one or more of triethylsilane, aminosilane, and trimethoxysilane.

[0015] By adopting the above technical solution, a silane coupling agent such as triethylsilane, aminosilane or trimethoxysilane is used as a modifier. The above silane coupling agent can combine with the Sn-OH formed in the modified filler to form a Si-O-Sn bond, so that the filler obtains a hydrophobic effect, thereby further reducing the possibility of agglomeration between the fillers, that is, the filler can be evenly dispersed in the coating and construct a conductive network.

[0016] Optionally, the antistatic agent also includes flaky graphene.

[0017] By adopting the above technical solution, graphene has a relatively good conductive effect. The introduction of flaky graphene can introduce a two-dimensional flaky structure into the coating, which can break the agglomeration of tin oxide and improve the dispersion effect of tin oxide. The introduction of two-dimensional flaky layers can increase the structural complexity of the conductive network, increase the electron migration channel, and make it easier for electrons to migrate between particles.

[0018] Optionally, the antistatic agent includes a support formed by partially supporting the tin oxide on the flaky graphene.

[0019] By adopting the above technical solution and using flaky graphene to load tin oxide, a one-dimensional-two-dimensional composite structure can be formed, thereby improving the dispersion effect of the antistatic agent, adding a complex structure to the conductive network, increasing the electron migration channel, and enhancing the conductive effect of the conductive network.

[0020] Optionally, the preparation method of the support is as follows: graphene is mixed with water to obtain a graphene solution, sodium carbonate and tin chloride are added to the graphene solution, heated, phenolic resin is added, and dried to obtain the support.

[0021] By adopting the above technical solution, phenolic resin is used to realize mutual loading between sodium carbonate and tin oxide, so as to improve the dispersion effect of the antistatic agent.

[0022] In a second aspect, the present application provides a method for preparing an anti-static crystal diamond coating, using the following technical solution: A method for preparing an antistatic crystal diamond coating is as follows: water, a defoamer and a film-forming aid are mixed separately, the rotation speed is adjusted, premixed to obtain a premix, bentonite, a suspending agent and a multifunctional auxiliary agent are added to the premix, the rotation speed is adjusted to obtain a viscous substance, acrylic emulsion, an inorganic emulsion, an antistatic agent and a filler are added to the viscous substance, the rotation speed is adjusted and stirred to obtain an intermediate, a thickener and a bactericide are added to the intermediate, and stirring is continued to obtain a crystal diamond coating.

[0023] By adopting the above technical solution and adjusting different rotation speeds, the paint can obtain suitable viscosity and coating effect.

[0024] In summary, this application has the following beneficial effects: 1. Since the present application adopts inorganic emulsion and acrylic emulsion as the base material of the coating, the problems of difficult storage, poor flexibility, poor weather resistance, long film-forming time, and low early strength of the coating are solved. At the same time, the present application preferably adopts tin oxide added to the coating as an antistatic agent. Tin oxide has the advantages of excellent conductivity and high specific surface area, which can improve the conductivity of the coating, thereby improving the antistatic effect of the coating, so that when the coating is applied to interior wall coating, the generation of static sparks is reduced, that is, the safety and fireproof effect of the coating are better. At the same time, with the cooperation of bentonite, filler and antistatic agent, a gradation effect can be formed in the coating, and the compactness of the coating formed by the coating is improved.

[0025] 2. In the present application, it is preferred to modify the filler with a tin-containing modifier, which can introduce tin atoms into the filler. Due to the excellent conductive effect of the tin atoms themselves, the filler obtains a conductive effect, and the filler network in the coating is transformed into a filler-conductive network, further improving the antistatic effect of the coating.

[0026] 3. Graphene is used as an antistatic agent in this application. Graphene has a relatively good conductive effect. The introduction of flaky graphene can introduce a two-dimensional flaky structure into the coating, which can break the agglomeration of tin oxide and improve the dispersion effect of tin oxide. The introduction of two-dimensional flaky layers can increase the structural complexity of the conductive network, increase the electron migration channel, and make it easier for electrons to migrate between particles. DETAILED DESCRIPTION

[0027] The present application is further described in detail below with reference to the embodiments.

[0028] Preparation Example Modified filler preparation example Preparation Example 1 The filler and water were mixed in an equal mass ratio to obtain a mixture, 1 mol / L tin chloride aqueous solution and 28% ammonia water were added to the mixture, the pH was adjusted to 11, the mixture was put into a reactor at 180° C. for 6 hours, dried, washed, filtered, and dried to obtain a modified filler with a coverage rate of 26%.

[0029] The filler in this preparation example includes crystal diamond and sintered sand in a mass ratio of 1:20.

[0030] Preparation Example 2 The filler and water were mixed in an equal mass ratio to obtain a mixture, 1 mol / L tin chloride aqueous solution and 28% ammonia water were added to the mixture, the pH was adjusted to 11, the mixture was put into a reactor at 180° C. for 6 hours, dried, washed, filtered, and dried to obtain a modified filler with a coverage rate of 30%.

[0031] The filler in this preparation example includes crystal diamond and sintered sand in a mass ratio of 1:20.

[0032] Preparation Example 3 The filler and water were mixed in an equal mass ratio to obtain a mixture, 1 mol / L tin chloride aqueous solution and 28% ammonia water were added to the mixture, the pH was adjusted to 11, the mixture was put into a reactor at 180° C. for 6 hours, dried, washed, filtered, and dried to obtain a modified filler with a coverage rate of 24%.

[0033] The filler in this preparation example includes crystal diamond and sintered sand in a mass ratio of 1:20.

[0034] Preparation Example 4 The filler and water are mixed in an equal mass ratio to obtain a mixture, 1 mol / L tin chloride aqueous solution and 28% ammonia water are added to the mixture, the pH is adjusted to 11, the mixture is put into a reactor at 180° C. for reaction for 6 hours, dried, washed, filtered, and dried to obtain an intermediate with a coverage rate of 26%, the intermediate is mixed with water, 5% by weight of KH550 is added, stirred, modified at 75° C. for 10 minutes, filtered, and dried to obtain a modified filler.

[0035] The filler in this preparation example is sintered sand.

[0036] Example of preparation of loading material Preparation Example 5 Graphene was mixed with water to obtain a 2.4 mg / mL graphene solution. 5 mg of sodium carbonate and 1 mg of tin chloride were added to the graphene solution, and the mixture was heated to 90° C., 0.1 g of phenolic resin was added, and the mixture was dried to obtain a loaded substance.

[0037] Preparation Example 6 Graphene was mixed with water to prepare a 2.4 mg / mL graphene solution, 5 mg of sodium carbonate and 1 mg of tin chloride were added to the graphene solution, the solution was heated to 90° C., 0.1 g of resorcinol and 0.2 g of glutaraldehyde were added, magnetic stirring was performed for 72 h, and freeze-dried to obtain a loaded substance.

[0038] Example Examples 1-3 On the one hand, the present application provides an antistatic crystal diamond coating, including acrylic emulsion, inorganic emulsion, bentonite, thickener, suspending agent, bactericide, multifunctional additive, film-forming additive, defoaming agent, antistatic agent, filler and water. The specific quality is shown in the table below, and the source of raw materials is shown in the table below.

[0039] The antistatic agent includes tin oxide, and the filler includes crystal diamond and sintered sand in a mass ratio of 1:20.

[0040] On the other hand, the present application provides a method for preparing an anti-static crystal diamond coating, which is as follows: water, a defoaming agent and a film-forming aid are mixed separately, the rotation speed is adjusted to 500 r / min, and premixed for 2-3 minutes to obtain a premix, bentonite, a suspending agent and a multifunctional auxiliary agent are added to the premix, the rotation speed is adjusted to 1100 r / min, and stirred for 20 minutes to obtain a viscous substance, acrylic emulsion, inorganic emulsion, antistatic agent and filler are added to the viscous substance, the rotation speed is adjusted to 1000 r / min and stirred for 7-8 minutes to obtain an intermediate, a thickener and a bactericide are added to the intermediate, and stirring is continued for 5 minutes to obtain a crystal diamond coating.

[0041] Table 1 Composition of Examples 1-3

[0042] Table 2 Raw material source composition

[0043] Example 4 On the one hand, the present application provides an antistatic crystal diamond paint, including 45kg acrylic emulsion, 120kg inorganic emulsion, 0.9kg bentonite, 2.4kg thickener, 3kg suspending agent, 1.8kg bactericide, 0.3kg multifunctional additive, 0.9kg film-forming additive, 0.9kg defoaming agent, 3.5kg antistatic agent, 210kg filler and 122.7kg water.

[0044] The antistatic agent includes tin oxide. The filler is the modified filler prepared in Preparation Example 1.

[0045] On the other hand, the present application provides a method for preparing an anti-static crystal diamond coating, which is as follows: water, a defoaming agent and a film-forming aid are mixed separately, the rotation speed is adjusted to 500 r / min, and premixed for 2-3 minutes to obtain a premix, bentonite, a suspending agent and a multifunctional auxiliary agent are added to the premix, the rotation speed is adjusted to 1100 r / min, and stirred for 20 minutes to obtain a viscous substance, acrylic emulsion, inorganic emulsion, antistatic agent and filler are added to the viscous substance, the rotation speed is adjusted to 1000 r / min and stirred for 7-8 minutes to obtain an intermediate, a thickener and a bactericide are added to the intermediate, and stirring is continued for 5 minutes to obtain a crystal diamond coating.

[0046] Example 5 The difference from Example 2 is that an equal mass of the modified filler prepared in Preparation Example 2 is used to replace the filler in Example 2 to prepare the antistatic coating.

[0047] Example 6 The difference from Example 2 is that an equal mass of the modified filler prepared in Preparation Example 3 is used to replace the filler in Example 2 to prepare the antistatic coating.

[0048] Example 7 The difference from Example 2 is that an equal mass of the modified filler prepared in Preparation Example 4 is used to replace the sintered sand in Example 2 to prepare the antistatic coating.

[0049] Example 8 On the one hand, the present application provides an antistatic crystal diamond paint, including 45kg acrylic emulsion, 120kg inorganic emulsion, 0.9kg bentonite, 2.4kg thickener, 3kg suspending agent, 1.8kg bactericide, 0.3kg multifunctional additive, 0.9kg film-forming additive, 0.9kg defoaming agent, 3.5kg antistatic agent, 210kg filler and 122.7kg water.

[0050] The antistatic agent is tin oxide and flake graphene. The filler includes crystal diamond and sintered sand in a mass ratio of 1:20.

[0051] On the other hand, the present application provides a method for preparing an anti-static crystal diamond coating, which is as follows: water, a defoaming agent and a film-forming aid are mixed separately, the rotation speed is adjusted to 500 r / min, and premixed for 2-3 minutes to obtain a premix, bentonite, a suspending agent and a multifunctional auxiliary agent are added to the premix, the rotation speed is adjusted to 1100 r / min, and stirred for 20 minutes to obtain a viscous substance, acrylic emulsion, inorganic emulsion, antistatic agent and filler are added to the viscous substance, the rotation speed is adjusted to 1000 r / min and stirred for 7-8 minutes to obtain an intermediate, a thickener and a bactericide are added to the intermediate, and stirring is continued for 5 minutes to obtain a crystal diamond coating.

[0052] Example 9 The difference from Example 2 is that the antistatic agent in this example includes tin oxide, flaky graphene and the load prepared in Preparation Example 5 in a mass ratio of 1:0.5:1 to prepare the antistatic coating.

[0053] Example 10 The difference from Example 2 is that the antistatic agent in this example includes tin oxide, flaky graphene and the load prepared in Preparation Example 6 in a mass ratio of 1:0.5:1 to prepare the antistatic coating.

[0054] Embodiment 11 On the one hand, the present application provides an antistatic crystal diamond paint, including 45kg acrylic emulsion, 120kg inorganic emulsion, 0.9kg bentonite, 2.4kg thickener, 3kg suspending agent, 1.8kg bactericide, 0.3kg multifunctional additive, 0.9kg film-forming additive, 0.9kg defoaming agent, 3.5kg antistatic agent, 210kg filler and 122.7kg water.

[0055] The antistatic agent includes tin oxide, graphene flakes and the support prepared in Preparation Example 6 in a mass ratio of 1:0.5:1. The filler is the modified filler prepared in Preparation Example 1.

[0056] On the other hand, the present application provides a method for preparing an anti-static crystal diamond coating, which is as follows: water, a defoaming agent and a film-forming aid are mixed separately, the rotation speed is adjusted to 500 r / min, and premixed for 2-3 minutes to obtain a premix, bentonite, a suspending agent and a multifunctional auxiliary agent are added to the premix, the rotation speed is adjusted to 1100 r / min, and stirred for 20 minutes to obtain a viscous substance, acrylic emulsion, inorganic emulsion, antistatic agent and filler are added to the viscous substance, the rotation speed is adjusted to 1000 r / min and stirred for 7-8 minutes to obtain an intermediate, a thickener and a bactericide are added to the intermediate, and stirring is continued for 5 minutes to obtain a crystal diamond coating.

[0057] Comparative Example Comparative Example 1 The difference between this comparative example and Example 3 is that no inorganic emulsion is added in this comparative example.

[0058] Comparative Example 2 The difference between this comparative example and Example 3 is that no antistatic agent is added in this comparative example.

[0059] Performance testing Resistivity test: GEST-121A volume surface resistance meter was used to measure the volume resistance of the antistatic coating.

[0060] Water resistance test: Refer to GB / T 1733-1993 to test the water resistance of the coating.

[0061] Table 3 Performance test

[0062] Combining the performance test comparison in Table 2, we can find that: 1. By comparing Examples 1-3 with Comparative Examples 1-2, it can be found that the antistatic effect of the coating obtained in Examples 1-3 is improved, which shows that the inorganic emulsion and acrylic emulsion are used as the base material of the coating in this application to solve the problems of difficult storage, poor flexibility, poor weather resistance, long film-forming time, and low early strength of the coating. At the same time, the application preferably uses tin oxide as an antistatic agent in the coating. Tin oxide has the advantages of excellent conductivity and high specific surface area, which can improve the conductivity of the coating, thereby improving the antistatic effect of the coating, so that when the coating is applied to interior wall coating, the generation of static sparks is reduced, that is, the safety and fireproof effect of the coating are better. At the same time, with the cooperation of bentonite, filler and antistatic agent, a grading effect can be formed in the coating, and the compactness of the coating formed by the coating is improved, so that the coating obtains an excellent water-resistant effect.

[0063] 2. By comparing Examples 4-6 with Example 2, it can be found that the antistatic effect of the coatings prepared in Examples 4-6 is improved, which indicates that the tin-containing modifier is used to modify the filler in the present application. The tin-containing modifier can introduce tin atoms into the filler. Due to the excellent conductive effect of the tin atoms themselves, the filler obtains a conductive effect, and the filler network in the coating is transformed into a filler-conductive network, further improving the antistatic effect of the coating. At an appropriate coverage rate, a better conductive effect, i.e., an antistatic effect, can be obtained.

[0064] 3. By comparing Example 7 with Example 2, it can be found that the antistatic effect of the coating prepared in Example 7 is improved, which means that the silane coupling agent used in the present application can combine with the Sn-OH formed in the modified filler to form a Si-O-Sn bond, so that the filler obtains a hydrophobic effect, thereby further reducing the possibility of agglomeration between the fillers, that is, the filler can be evenly dispersed in the coating and construct a conductive network.

[0065] 4. By comparing Example 8 with Example 2, it can be found that the antistatic effect of the coating prepared in Example 8 is improved, which shows that the introduction of flaky graphene in the present application can introduce a two-dimensional flaky structure into the coating, break the agglomeration of tin oxide, and improve the dispersion effect of tin oxide. The introduction of two-dimensional flaky layers can increase the structural complexity of the conductive network, increase the electron migration channel, and make it easier for electrons to migrate between particles.

[0066] 5. By comparing Examples 9-11 with Example 2, it can be found that the antistatic effect of the coatings prepared in Examples 9-11 is improved, which means that the use of flaky graphene loaded with tin oxide in the present application can form a one-dimensional-two-dimensional composite structure, improve the dispersion effect of the antistatic agent, and increase the complex structure in the conductive network, increase the electron migration channel, and enhance the conductive effect of the conductive network.

[0067] Since the graphene is carbonized in Preparation Example 6, the carrier forms a three-dimensional structure, thereby forming a composite structure of three-dimensional porous, two-dimensional lamellar and one-dimensional tin oxide in the coating, further increasing the complexity of the conductive network and the electron transition path, so as to further improve the antistatic effect of the interior wall coating.

[0068] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An antistatic crystal diamond coating, characterized in that: The invention comprises the following raw materials in parts by weight: 40-50 parts of acrylic emulsion; 115-125 parts of inorganic emulsion; 0.8-1.0 part of bentonite; 2-3 parts thickener; 2-4 parts of suspending agent; 1.5-2.5 parts of fungicide; Multifunctional additive 0.1-0.5 parts; Film-forming aid 0.8-1.0 part; Defoaming agent 0.8-1.0 part; 2-5 parts of antistatic agent; 200-210 parts of filler; 122-123 parts of water; The antistatic agent includes tin oxide.

2. The antistatic diamond coating according to claim 1, characterized in that: The filler includes crystal diamond and sintered sand.

3. The antistatic diamond coating according to claim 1, characterized in that: The filler is a modified filler modified by a modifier, and the modifier is a tin-containing modifier.

4. The antistatic diamond coating according to claim 3, characterized in that: The modification treatment steps are as follows: mixing the filler with water to obtain a mixture, adding a tin-containing modifier and ammonia water to the mixture, adjusting the pH, putting it into a reactor for reaction, drying, washing, filtering, and drying to obtain a modified filler.

5. The antistatic crystal diamond coating according to claim 4, characterized in that: The coverage rate of the modified filler is 26-30%.

6. The antistatic crystal diamond coating according to claim 3, characterized in that: The modifier further comprises any one or more of triethylsilane, aminosilane and trimethoxysilane.

7. The antistatic diamond coating according to claim 1, characterized in that: The antistatic agent also includes flake graphene.

8. The antistatic crystal diamond coating according to claim 7, characterized in that: The antistatic agent includes a supported substance formed by partially supporting the tin oxide on the flaky graphene.

9. The antistatic crystal diamond coating according to claim 8, characterized in that: The preparation method of the support is as follows: graphene is mixed with water to obtain a graphene solution, sodium carbonate and tin chloride are added to the graphene solution, heated, phenolic resin is added, and dried to obtain the support.

10. The method for preparing an antistatic crystal diamond coating according to any one of claims 1 to 9, characterized in that: The details are as follows: Water, a defoamer and a film-forming aid are mixed separately, the speed is adjusted, and premixing is performed to obtain a premix; bentonite, a suspending agent and a multifunctional aid are added to the premix, and the speed is adjusted to obtain a viscous substance; acrylic emulsion, an inorganic emulsion, an antistatic agent and a filler are added to the viscous substance, the speed is adjusted and stirred to obtain an intermediate; a thickener and a bactericide are added to the intermediate, and stirring is continued to obtain a crystal diamond coating.